Cybersecurity of Industrial Automation and Control System (IACS) Networks in Biomass Power Plants - Montri Wiboonrat (My University, 2023)
During the COVID-19 pandemic, the Industrial Automation Control Systems (IACS) have to change procedures in day-by-day operations. Biomass power plants (BPP) cannot avoid this crisis as well. This research aims to solve the problems of BPP operations. The cybersecurity integration between Information Technology (IT) and Operations Technology (OT) was performed by combining of IEC 62443 series, NIST.800.82r2, ISA-95, and Purdue Model as guideline framework for cybersecurity of IACS networks as vulnerability protection. This research purposes two cybersecurity protection models called “Spectrum Security”. Spectrum Security - SL2 was designed for minimum detection and protection for IACS. Spectrum Security - SL4 was designed for maximum detection and protection for IACS and fault tolerance operations availability of cybersecurity vulnerability. However, the consequence of Fault Tolerance is a double investment in cybersecurity detection and protection systems.
Keywords: Smart Grid Security and Resilience; Industrial Automation and Control Systems; Real-time simulation and control systems